Environmental Applications of Boron‐Doped Diamond Electrodes: 2. Soil Remediation and Sensing Applications. Issue 8 (28th March 2019) - Trellu, Clément; Chakraborty, Shampa; Nidheesh, P. V.; Oturan, Mehmet A.
Abstract: The chemical stability and electrocatalytic properties of boron‐doped diamond (BDD) electrodes give rise to various applications. While wastewater treatment is the most widely studied field, the use of BDD for soil remediation and environmental sensing is currently investigated more and more. With regards to soil remediation, promising results have been reported for the treatment of soil washing solutions. Anodic oxidation using BDD at high current density allows high mineralization rates of biorefractory soil pollutants and extracting agents to be reached. At low current density, selective degradation of target pollutants has been achieved, thus allowing the reuse of extracting agents for further soil washing steps. BDD‐based electrochemical sensors have been studied for chemical oxygen demand determination, pesticide/pharmaceutical detection as well as other applications such as pH, O2 and analysis of various organic and inorganic compounds. Low detection limits, wide linear ranges and low standard deviations have been achieved. The main reasons behind the superiority of BDD sensors are the chemical stability, wide applicability and resistance of BDD towards biofouling. The beauty of BDD sensing is that it can work for a variety of organic and inorganic compounds under many physicochemical parameters. Abstract : Makes sense : Applications of boron‐doped diamond (BDD) electrodes in various areas have been explored in recent decades. This review examines in detail the applications of BDD in soil remediation as well as electrochemical sensing.